Association of Serum β-Hydroxybutyrate and Coronary Artery Disease in an Urban Chinese Population - Mu, Hongna; Yang, Ruiyue; Wang, Siming; Zhang, Wenduo; Wang, Xinyue; Li, Hongxia; Dong, Jun; Chen, Wenxiang; Yu, Xue; Ji, Fusui (Frontiers in Nutrition, 2022)
Ketone bodies, including β-hydroxybutyrate, acetoacetate, and acetone, can substitute and alternate with glucose under conditions of fuel/food deficiency. Ketone-body metabolism is increased in a myriad of tissue-metabolism disorders. Perturbations in metabolism are major contributors to coronary artery disease (CAD). We investigated the association of β-hydroxybutyrate with CAD. A total of 2,970 people of Chinese Han ethnicity were enrolled. The Gensini score was calculated for all patients who had positive findings. The serum level of β-hydroxybutyrate and other laboratory parameters were measured. The association of serum level of metabolites with traditionary risk factors and CAD severity were analyzed. β-hydroxybutyrate was found to be associated with some traditional risk factors of CAD and CAD severity, as determined by the Gensini score or number of diseased regions. Moreover, β-hydroxybutyrate was associated with the T3/T1 tertiles of the Gensini score after adjustment for traditional risk factors by multivariable logistic regression analysis. The association of β-hydroxybutyrate with CAD severity was more obvious in females. Taken together, these data suggest that the circulating β-hydroxybutyrate level is independently associated with CAD severity, and that this association is more pronounced in females.